Analyzing the Impact of Covid-19 on Indian Airline Stocks: An Empirical Analysis using Event Study Methodology - sheikh, jabir yousuf sheikh; Kanungo, Ranjana (International Journal of Finance Research, 2023)
The outburst of Covid-19 pandemic has slowed down the economic progress both in developed and developing nations. Since its outburst, the stock markets have declined all around the globe. However, some industries become profoundly weak while others proceed to perform well even in the crisis period. Given this new phenomena we try to study the short-term effects of the outburst of new contagious disease COVID-19, on four BSE listed aviation companies in India by employing event study methodology. The outcomes reveal that Indian aviation stock returns drop more significantly than the BSE stock market returns in response to the four main COVID-19 press statements that were made during first half of year 2020. Generally, stockholders respond contrarily in the four selected events. The strong over response shown by the investors is noted during the on-event period of the announcements made by World Health Organization and the Indian government. Besides, the results endorses that investors of Indigo and Spicejet were more reactive to the announcements made related to Covid-19 outbreak. The findings demand for instant policy framework in order to lighten the bad effects of the pandemic in the airline sector in India